Polyurethane hot melt adhesive with excellent bonding performance and capable of being electrically disassembled as well as preparation method and application of polyurethane hot melt adhesive

By integrating oxide-based or sulfide-based solid electrolytes with silane coupling agents, the adhesive addresses bonding strength and resistance issues, providing a detachable and reliable polyurethane hot melt adhesive for electronic products.

CN119193082AActive Publication Date: 2024-12-27XIAMEN WELDTONE TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411459628.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-27
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Existing polyurethane hot melt adhesives used in electronic products face challenges in achieving high bonding strength while being detachable under power-on conditions, with issues in heat resistance, high temperature resistance, and humidity resistance, and the use of liquid electrolytes compromises bonding strength.

Method used

Incorporating a specific ratio of oxide-based or sulfide-based solid electrolytes with silane coupling agents into the polyurethane hot melt adhesive, ensuring even dispersion and reinforcing the adhesive's structure, while maintaining high bonding strength and resistance properties.

Benefits of technology

The adhesive achieves high bonding strength, good heat resistance, and high humidity resistance, with the ability to be electrically disassembled without significant strength loss, suitable for electronic product assembly and disassembly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091501460000131
    Figure BDA0005091501460000131
Patent Text Reader

Abstract

The invention belongs to the technical field of polyurethane hot melt adhesives, and particularly relates to an electrically-detachable polyurethane hot melt adhesive with excellent bonding performance as well as a preparation method and application of the electrically-detachable polyurethane hot melt adhesive. The polyurethane hot melt adhesive is prepared from the following raw materials: a solid electrolyte, a polyol compound, a polyisocyanate compound, a silane coupling agent and optional tackifying resin, a catalyst and a water absorbent, the mass ratio of the solid electrolyte to the polyol compound to the silane coupling agent is (5-35): 100: (5-25). The key of the invention lies in that a specific solid electrolyte (oxide-based solid electrolyte and / or sulfide-based solid electrolyte) is introduced into a polyurethane hot melt adhesive system, and the proportion of the solid electrolyte, the polyol compound and the silane coupling agent is regulated and controlled, so that the obtained polyurethane hot melt adhesive not only has the electrical disassembly performance, but also has the advantages of good electrical disassembly performance and good mechanical property. The bonding strength is high, and the heat resistance and the high-temperature and high-humidity resistance are good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane hot melt adhesives, and specifically relates to a polyurethane hot melt adhesive with excellent bonding performance and electrical disassembly, and a preparation method and application thereof. Background Art

[0002] In the bonding application of electronic products, polyurethane hot melt adhesive is widely used in electronic products such as smart phones, tablets, smart watches, TWS headphones, etc. because it can achieve high bonding strength after curing. However, in the actual production process of electronic products, it is often necessary to disassemble some of the bonded parts for reassembly, repair, recycling, etc. The main resin of polyurethane hot melt adhesive is an oligomer terminated by isocyanate groups, and the isocyanate groups can react with moisture in the air to complete the curing to form a cross-linked chemical structure, thereby achieving high bonding strength. The covalent bond obtained by the reaction of isocyanate groups with moisture is irreversible, and the cross-linked structure is difficult to be destroyed. It is usually difficult to disassemble after complete curing, and it is often necessary to use large external forces, high temperatures, chemical reagents, etc. to achieve the purpose of disassembly, which is easy to cause damage to the bonding substrate during the disassembly process. Since electronic product parts are often of high value, this requires finding a more gentle way to disassemble. In recent years, there is a technology that adds alkali metal salts and solvated matrix to polyurethane hot melt adhesive to form a liquid electrolyte, giving the polyurethane hot melt adhesive the function of being disassembled under power-on conditions, thereby achieving gentle disassembly without damaging the electronic bonding substrate. However, although the existing polyurethane hot melt adhesive that can be disassembled under power-on conditions has the function of being disassembled under power-on conditions, it still has a large gap with the traditional widely used polyurethane hot melt adhesive in terms of bonding strength, curing speed, heat resistance, high temperature and high humidity resistance and other properties, which limits the promotion and use of such electrically disassembled polyurethane hot melt adhesives. Summary of the invention

[0003] The purpose of the present invention is to provide a polyurethane hot melt adhesive with high bonding strength, good heat resistance and high temperature and humidity resistance, and electrically disassembled, as well as a preparation method and application thereof, in view of the shortcomings of the prior art polyurethane hot melt adhesive that can be electrically disassembled, such as poor bonding strength and poor heat resistance and high temperature and humidity resistance.

[0004] In the first aspect, the present invention provides a polyurethane hot melt adhesive, wherein the raw materials for preparing the polyurethane hot melt adhesive contain a solid electrolyte, a polyol compound, a polyisocyanate compound, a silane coupling agent, and optionally a tackifying resin, a catalyst, and a water absorbent; the solid electrolyte is an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte; the mass ratio of the solid electrolyte, the polyol compound, and the silane coupling agent is (5-35):100:(5-25).

[0005] In some specific embodiments, the content of the solid electrolyte is 5 to 15 parts by weight, the content of the polyol compound is 45 to 65 parts by weight, the content of the polyisocyanate compound is 10 to 20 parts by weight, the content of the silane coupling agent is 5 to 10 parts by weight, the content of the tackifying resin is 0 to 15 parts by weight, the content of the catalyst is 0 to 2 parts by weight, and the content of the water absorbent is 0 to 2 parts by weight.

[0006] In some specific embodiments, the ionic conductivity of the solid electrolyte at room temperature is 10 -4 S / cm or more.

[0007] In some specific embodiments, the D50 or D90 particle size of the solid electrolyte is 0.3 to 30 μm.

[0008] In some specific embodiments, the number average molecular weight of the polyol compound is 1000 to 4000 g / mol.

[0009] In some specific embodiments, the polyol compound is selected from at least one of polyester polyols, polyether polyols, polycarbonate polyols and polyalkylene polyols.

[0010] In some specific embodiments, the polyisocyanate compound is selected from at least one of isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, hydrogenated xylylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-pentane diisocyanate, 1,4-phenylene diisocyanate, meta-xylylene diisocyanate, tetramethylxylylene diisocyanate, norbornane dimethylene isocyanate, lysine diisocyanate, triphenylmethane triisocyanate, thiophosphoric acid triphenyl isocyanate and 1,6,11-undecane triisocyanate.

[0011] In some specific embodiments, the tackifying resin is selected from at least one of thermoplastic acrylic resin, polyurethane resin, rosin resin, petroleum resin, terpene resin, EVA resin, and amorphous polyolefin resin.

[0012] In some specific embodiments, the silane coupling agent is selected from 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl methyl diethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl triethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-aminopropyl trimethoxysilane, 3- At least one of aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and 3-isocyanatepropyltrimethoxysilane.

[0013] In some specific embodiments, the catalyst is selected from at least one of dibutyltin dilaurate, stannous octoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether.

[0014] In some specific embodiments, the water absorbent is selected from at least one of a molecular sieve desiccant, an oxazolidine desiccant, p-toluenesulfonyl isocyanate and triethyl orthoformate.

[0015] In a second aspect, the present invention provides a method for preparing the above-mentioned polyurethane hot melt adhesive, which comprises uniformly mixing a solid electrolyte, a polyol compound, a polyisocyanate compound, a silane coupling agent, and optional tackifying resins, catalysts, and water absorbents to obtain a polyurethane hot melt adhesive.

[0016] In a third aspect, the present invention also provides the use of the above-mentioned polyurethane hot melt adhesive in bonding electronic products.

[0017] In existing polyurethane hot melt adhesives, detachable properties are usually achieved by adding liquid electrolytes. However, although the use of liquid electrolytes can give polyurethane hot melt adhesives the ability to be detached when powered on, it will seriously affect the bonding strength of the polyurethane hot melt adhesive. In this regard, after in-depth research, the inventors of the present invention found that one of the main reasons for the significant decrease in the bonding strength of polyurethane hot melt adhesives is that the liquid electrolyte is a liquid substance and is difficult to solidify. After the polyurethane hot melt adhesive is completely solidified, the unsolidified liquid electrolyte will remain in the curing system to form a "plasticizer", which changes the internal structure of the curing system. The presence of this "plasticizer" has a large negative impact on the bonding strength and will greatly reduce the bonding performance of the polyurethane hot melt adhesive; in addition, due to the poor compatibility between inorganic solid electrolyte materials and organic polyurethane hot melt adhesives, it is usually difficult to evenly disperse them in the polyurethane hot melt adhesive system, which limits its application in electrically disassembled polyurethane hot melt adhesives.

[0018] The key to the present invention is to disregard the limitation of the traditional concept that inorganic solid electrolytes are difficult to be evenly dispersed in the polyurethane hot melt adhesive system and should be used with caution. A specific solid electrolyte (oxide-based solid electrolyte and / or sulfide-based solid electrolyte) is introduced into the polyurethane hot melt adhesive system in the presence of a silane coupling agent, and the ratio between the solid electrolyte, the polyol compound and the silane coupling agent is regulated. The resulting polyurethane hot melt adhesive not only has the property of being electrically disassembled, but also has the advantages of high bonding strength and good heat resistance and high temperature and high humidity resistance. The reasons are speculated to be: oxide-based solid electrolytes and sulfide-based solid electrolytes themselves have high ionic conductivity in the solid state, and can undergo Faraday electrochemical reactions under power-on conditions, weakening the bonding force at the adhesive bonding interface, thereby giving the polyurethane hot melt adhesive detachable properties. In addition, these two specific solid electrolytes, oxide-based solid electrolytes and sulfide-based solid electrolytes, have good compatibility with polyurethane hot melt adhesives under the synergistic effect of silane coupling agents and can be well dispersed in the polyurethane hot melt adhesive system. At the same time, oxide-based solid electrolytes and sulfide-based solid electrolytes will not form "plasticizers" after the polyurethane hot melt adhesive is cured, causing changes in its internal structure to affect the bonding strength. On the contrary, oxide-based solid electrolytes and sulfide-based solid electrolytes themselves can also serve as fillers to reinforce the colloid, thereby improving the bonding properties of the polyurethane hot melt adhesive and improving the bonding strength, heat resistance, and high temperature and high humidity resistance. In summary, the polyurethane hot melt adhesive provided by the present invention has high bonding strength and good heat resistance, high temperature and high humidity resistance, and can be electrically disassembled, which provides a solution, product, and method for application scenarios with high requirements for bonding reliability and the need for adhesive disassembly during actual production processes. DETAILED DESCRIPTION

[0019] The raw materials for preparing the polyurethane hot melt adhesive provided by the present invention contain a solid electrolyte, a polyol compound, a polyisocyanate compound, a silane coupling agent, and optional tackifying resins, catalysts, and water absorbents. The mass ratio of the solid electrolyte to the polyol compound is (5-35):100, such as 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, or any value therebetween. The mass ratio of the polyol compound to the silane coupling agent is 100:(5-25), such as 100:5, 100:10, 100:15, 100:20, 100:25, or any value therebetween. The solid electrolyte is an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte. Among them, the structural features of the oxide-based solid electrolyte are preferably selected from at least one of NASICON type, garnet type, and perovskite type. The structural characteristics of the sulfide-based solid electrolyte are preferably at least one of amorphous, crystalline and glass-ceramic.

[0020] In the present invention, the amount of the solid electrolyte is preferably 5 to 15 parts by weight, such as 5, 8, 10, 12, 15 parts by weight or any value therebetween; the amount of the polyol compound is preferably 45 to 65 parts by weight, such as 45, 48, 50, 52, 55, 58, 60, 62, 65 parts by weight or any value therebetween; the amount of the polyisocyanate compound is preferably 10 to 20 parts by weight, such as 10, 12, 15, 18, 20 parts by weight or any value therebetween; the amount of the silane coupling agent is preferably 5 to 10 parts by weight , such as 5, 6, 7, 8, 9, 10 parts by weight or any value therebetween; the amount of the tackifying resin is preferably 0 to 15 parts by weight, such as 0, 5, 8, 10, 12, 15 parts by weight or any value therebetween; the amount of the catalyst is preferably 0 to 2 parts by weight, such as 0, 0.1, 0.2, 0.5, 0.8, 1, 1.5, 2 parts by weight or any value therebetween; the amount of the water absorbent is preferably 0 to 2 parts by weight, such as 0, 0.1, 0.2, 0.5, 0.8, 1, 1.5, 2 parts by weight or any value therebetween.

[0021] In the present invention, the solid electrolyte is an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte. The ionic conductivity of the oxide-based solid electrolyte and / or the sulfide-based solid electrolyte at room temperature is generally 10 -4S / cm or more, and its source and type can be various existing options. The D50 or D90 particle size of the solid electrolyte is preferably 0.3 to 30 μm, such as 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm or any value therebetween. When the D50 or D90 particle size of the solid electrolyte is within the above preferred range, it is more conducive to the uniform dispersion of the solid electrolyte in the polyurethane hot melt adhesive system, giving it good electrical disassembly performance, and it is also more conducive to the reinforcing role of the solid electrolyte as a filler, and cooperating with other raw material components to improve the bonding strength, heat resistance and high temperature and high humidity resistance of the polyurethane hot melt adhesive system. The term "D50 or D90 particle size" refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50% or 90%.

[0022] In the present invention, the number average molecular weight (Mn) of the polyol compound is preferably 1000-4000 g / mol, such as 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol, 3000 g / mol, 3500 g / mol, 4000 g / mol or any value therebetween. The type and source of the polyol compound can be various existing choices, preferably at least one of polyester polyol, polyether polyol, polycarbonate polyol and polyalkylene polyol. Specifically, the polyester polyol can be a polyester polyol obtained by the reaction of a polycarboxylic acid and a polyol, or a poly-ε-caprolactone polyol obtained by ring-opening polymerization of ε-caprolactone. Wherein, the polycarboxylic acid is preferably at least one of terephthalic acid, isophthalic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decamethylene dicarboxylic acid and dodecamethylene dicarboxylic acid. The polyol is preferably at least one of ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol and cyclohexanediol. The polyether polyol may be at least one of a random copolymer, a block copolymer and a bisphenol-type polyoxyalkylene modified body of ethylene glycol, propylene glycol, tetrahydrofuran, 3-methyltetrahydrofuran or a derivative thereof. Wherein, the bisphenol-type polyoxyalkylene modified body is a polyether polyol obtained by adding alkylene oxide to the active hydrogen portion of the bisphenol-type molecular skeleton, and may be a random copolymer and / or a block copolymer. The alkylene oxide is preferably at least one of ethylene oxide, propylene oxide, butylene oxide and isobutylene oxide. The carbonate polyol can be exemplarily polycarbonate 1,6-hexanediol ester diol, polycarbonate-1,4-butanediol-1,6 hexanediol ester diol, polycarbonate-1,5-pentanediol-1,6 hexanediol ester diol, polycarbonate caprolactone hexanediol, polycarbonate-1,4-cyclohexanedimethanol-1,6 hexanediol ester diol, polyethylene carbonate diol, polypropylene carbonate diol, polybutylene carbonate diol and polyhexane carbonate diol. The polyalkylene polyol can be exemplarily polybutadiene polyol, hydrogenated polybutadiene polyol and hydrogenated polyisoprene polyol.

[0023] In the present invention, the type and source of the polyisocyanate compound can be various existing options, preferably at least one selected from isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, hydrogenated xylylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-pentane diisocyanate, 1,4-phenylene diisocyanate, meta-xylylene diisocyanate, tetramethylxylylene diisocyanate, norbornane dimethylene isocyanate, lysine diisocyanate, triphenylmethane triisocyanate, thiophosphoric acid triphenyl isocyanate and 1,6,11-undecane triisocyanate.

[0024] In the present invention, the type and source of the tackifying resin can be various existing options, preferably at least one selected from thermoplastic acrylic resin, polyurethane resin, rosin resin, petroleum resin, terpene resin, EVA resin, and amorphous polyolefin resin.

[0025] In the present invention, the type and source of the silane coupling agent can be various existing options, preferably at least one of mercaptosilane, epoxysilane, aminosilane, alkenylsilane and isocyanate silane, and specific examples thereof include but are not limited to: 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxy At least one of propoxypropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(methyl)acryloxypropyltrimethoxysilane, 3-(methyl)acryloxypropyltriethoxysilane, 3-(methyl)acryloxypropylmethyldimethoxysilane, 3-(methyl)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and 3-isocyanatepropyltrimethoxysilane. The addition of a silane coupling agent helps to promote the uniform dispersion of the solid electrolyte in the polyurethane hot melt adhesive system, thereby facilitating the electrical disassembly performance of the polyurethane hot melt adhesive system.

[0026] In the present invention, the type and source of the catalyst can be various existing options, preferably at least one selected from dibutyltin dilaurate, stannous octoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether.

[0027] In the present invention, the type and source of the water absorbent can be various existing options, preferably at least one selected from molecular sieve desiccant, oxazolidine dehydrating agent, p-toluenesulfonyl isocyanate and triethyl orthoformate.

[0028] The preparation method of the polyurethane hot melt adhesive provided by the present invention comprises uniformly mixing a solid electrolyte, a polyol compound, a polyisocyanate compound, a silane coupling agent, and an optional tackifying resin, a catalyst, and a water absorbent to obtain a polyurethane hot melt adhesive. The present invention does not particularly limit the mixing conditions. In a preferred embodiment, the mixing method specifically comprises the following steps: S1. After mixing the solid electrolyte, the polyol compound, the silane coupling agent, and the optional tackifying resin and the water absorbent, the mixture is subjected to vacuum dehydration treatment to obtain a pretreated product; S2. The pretreated product is mixed with a polyisocyanate compound and an optional catalyst to obtain a polyurethane hot melt adhesive.

[0029] In the preparation process of the above-mentioned polyurethane hot melt adhesive, in step S1, the conditions for vacuum dehydration include: the temperature is preferably 100-120°C, such as 100°C, 105°C, 110°C, 115°C, 120°C or any value therebetween; the time is preferably 1-5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween; the stirring speed is preferably 100-200r / min, such as 100r / min, 120r / min, 150r / min, 180r / min, 200r / min or any value therebetween.

[0030] In the preparation process of the above-mentioned polyurethane hot melt adhesive, in step S2, the mixing treatment conditions include: the temperature is preferably 70-90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C or any value therebetween; the time is preferably 1-5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween; the stirring speed is preferably 100-200r / min, such as 100r / min, 120r / min, 150r / min, 180r / min, 200r / min or any value therebetween.

[0031] The reactive polyurethane hot melt adhesive provided by the present invention can be applied to an adhesive substrate that can be electrified, and the voltage for electrification and disassembly can be 1 to 100V, such as 1V, 5V, 9V, 10V, 20V, 50V, 60V, 80V, 100V or any value therebetween, and the time for electrification and disassembly can be 1s to 60min, such as 1s, 2s, 5s, 10s, 30s, 50s, 1min, 2min, 5min, 10min, 20min, 30min, 40min, 50min, 60min or any value therebetween. In addition, the adhesive substrate used by the reactive polyurethane hot melt adhesive is a conductive substrate.

[0032] The present invention will be described in detail below through specific embodiments.

[0033] The parts involved in the following examples and comparative examples are all parts by weight.

[0034] The raw materials and sources in the following examples and comparative examples are as follows:

[0035] Polyhexanediol adipate diol, purchased from Qingdao Xinyutian Chemical Company, brand POL-538, Mn = 3000g / mol; polyoxypropylene ether diol, purchased from Dow Chemical Company, brand Voranol-2120, Mn = 2000g / mol; polybutylene adipate diol, purchased from Qingdao Xinyutian Chemical Company, brand POL-3112, Mn = 1000g / mol; polyneopentyl adipate diol, purchased from Qingdao Xinyutian Chemical Company, brand POL-756, Mn = 2000g / mol; polycarbonate-1,5-pentanediol-1,6-hexanediol ester diol, purchased from Ube Industries, brand ETERNACOLL PH-100, Mn = 1000 g / mol; polycaprolactone diol, purchased from Perstorp, brand CAPA-2200P, Mn = 2000 g / mol; polytetramethylene ether diol, purchased from South Korea PTG, brand PTMEG 3000, Mn = 3000 g / mol; polyhexanediol adipate diol, purchased from Qingdao Xinyutian Chemical Company, brand POL-5112, Mn = 1000 g / mol; polybutylene adipate diol, purchased from Qingdao Xinyutian Chemical Company, brand POL-356, Mn = 2000 g / mol.

[0036] NASICON oxide-based solid electrolyte LATP, D50 = 0.3 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LATP-300, ionic conductivity ≥ 6*10 at room temperature -4S / cm; sulfide-based solid electrolyte FL-LPSC, D50 = 30 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LPSC-30000, the ionic conductivity at room temperature is 1*10 -2 S / cm; garnet oxide-based solid electrolyte FL-GTEP, D50 = 0.5 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand GTEP-500, ionic conductivity ≥ 8*10 at room temperature -4 S / cm; sulfide-based solid electrolyte FL-LPSC, D90 = 20 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LPSC-20000, with an ionic conductivity of 6*10 at room temperature -3 S / cm; NASICON oxide-based solid electrolyte LATP, D50 = 0.6 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LATP-600, ionic conductivity ≥ 6*10 at room temperature -4 S / cm; NASICON oxide-based solid electrolyte LATP, D50 = 0.1 μm, purchased from Bluegoo New Energy Technology Co., Ltd., brand LG1117, ionic conductivity at room temperature is 5*10 -4 S / cm~1*10 - 3 S / cm; sulfide-based solid electrolyte LGPS, D50 = 50 μm, purchased from Shenzhen ASML New Energy Co., Ltd., brand LGPS-50 μm, ionic conductivity at room temperature is ≥7*10 -3 S / cm; Polyethylene oxide PEO solid electrolyte, purchased from Cluder, brand E-30, ionic conductivity at room temperature is 6.29*10 -6 S / cm.

[0037] The p-toluenesulfonyl isocyanate water absorbent was purchased from Borchers, Germany, with the brand name Additive TI; the triethyl orthoformate water absorbent was purchased from Borchers, Germany, with the brand name Additive OF; the adsorbent molecular sieve water absorbent was purchased from ARkEMA, with the brand name Siliporite SA1702.

[0038] Example 1

[0039] 40.22 parts of polyhexanediol adipate diol POL-538 (Mn=3000 g / mol), 22.98 parts of polyoxypropylene ether diol Voranol-2120 (Mn=2000 g / mol), 10.00 parts of acrylic resin BR-106, 7.50 parts of NASICON-type oxide-based solid electrolyte LATP (D50=0.3 μm), 7.00 parts of 3-mercaptopropyltrimethoxysilane, and 0.50 parts of water absorbent Additive TI were added to a reaction bottle, heated to 110°C, and vacuum dehydrated for 2 hours under stirring conditions of 150 r / min; then cooled to 80°C, 11.49 parts of 4,4'-diphenylmethane diisocyanate (MDI) and 0.30 parts of stannous octoate were added, and the reaction was carried out under stirring conditions of 150 r / min for 2 hours before discharging to obtain a polyurethane hot melt adhesive, which was vacuum sealed and stored.

[0040] Example 2

[0041] 19.95 parts of polybutylene adipate diol POL-3112 (Mn=1000 g / mol), 39.90 parts of polyneopentyl adipate diol POL-756 (Mn=2000 g / mol), 10.00 parts of thermoplastic polyurethane resin Pearlbond523, 5.00 parts of sulfide-based solid electrolyte FL-LPSC (D50=30 μm), 5.00 parts of 3-glycidoxypropyltrimethoxysilane, and 0.10 parts of water absorbent Additive OF were added to a reaction bottle, heated to 110° C., and vacuum dehydrated for 2 hours under stirring conditions of 150 r / min; then cooled to 80° C., 19.95 parts of 4,4'-diphenylmethane diisocyanate (MDI) and 0.10 parts of dibutyltin dilaurate were added, and the reaction was carried out under stirring conditions of 150 r / min for 2 hours before discharging to obtain a polyurethane hot melt adhesive, which was vacuum sealed and stored.

[0042] Example 3

[0043] 15.80 parts of polycarbonate-1,5-pentanediol-1,6-hexanediol ester ETERNACOLL PH-100 (Mn=1000 g / mol), 31.59 parts of polycaprolactone diol CAPA-2200P (Mn=2000 g / mol), 15.00 parts of acrylic resin BM751, 15.00 parts of garnet-type oxide-based solid electrolyte FL-GTEP (D50=0.5 μm), 10.00 parts of 3-glycidoxypropyltrimethoxysilane, and 1.00 parts of water absorbent Siliporite SA1702 was added to the reaction bottle, heated to 110°C, and vacuum dehydrated for 2 hours at 150 r / min. Then the temperature was lowered to 80°C, 10.61 parts of hexamethylene diisocyanate (HDI) and 1.00 parts of 2,2-dimorpholinyl diethyl ether were added, and the reaction was carried out at 150 r / min. The polyurethane hot melt adhesive was obtained and stored in a vacuum sealed state.

[0044] Example 4

[0045] 43.15 parts of polytetramethylene glycol PTMEG 3000 (Mn=3000 g / mol), 14.38 parts of polyhexane adipate glycol POL-5112 (Mn=1000 g / mol), 8.00 parts of amorphous polyolefin APAO resin VESTOPLAST 520, 10.00 parts of sulfide-based solid electrolyte FL-LPSC (D90=20 μm), 8.50 parts of vinyltrimethoxysilane, and 1.20 parts of water absorbent Additive TI were added to a reaction bottle, heated to 110°C, and vacuum dehydrated for 2 hours under stirring conditions of 150 r / min; then the temperature was lowered to 80°C, 12.77 parts of isophorone diisocyanate (IPDI) and 2.00 parts of dibutyltin dilaurate were added, and the reaction was carried out under stirring conditions of 150 r / min for 2 hours before discharging to obtain a polyurethane hot melt adhesive, which was vacuum sealed and stored.

[0046] Example 5

[0047] 26.90 parts of polyoxypropylene ether diol Voranol-2120 (Mn=2000 g / mol), 26.90 parts of polybutylene adipate diol POL-356 (Mn=2000 g / mol), 12.00 parts of thermoplastic polyurethane resin Pearlbond539, 11.00 parts of NASICON type oxide-based solid electrolyte LATP (D50=0.6 μm), 6.80 parts of 3-mercaptopropyltrimethoxysilane, and 0.80 parts of water absorbent Additive OF were added to a reaction bottle, heated to 110°C, and vacuum dehydrated for 2 hours under stirring conditions of 150 r / min; then cooled to 80°C, 14.10 parts of 4,4-diisocyanate dicyclohexylmethane (HMDI) and 1.50 parts of stannous octoate were added, and the reaction was carried out under stirring conditions of 150 r / min for 2 hours before discharging to obtain a polyurethane hot melt adhesive, which was vacuum sealed and stored.

[0048] Example 6

[0049] A polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the same amount of NASICON-type oxide-based solid electrolyte LATP with D50=0.1μm was used instead of NASICON-type oxide-based solid electrolyte LATP with D50=0.3μm, and the other conditions were the same as those in Example 1, thereby preparing a polyurethane hot melt adhesive, which was vacuum-sealed and stored.

[0050] Example 7

[0051] A polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the same amount of sulfide-based solid electrolyte LGPS-50μm with D50=50μm was used instead of NASICON-type oxide-based solid electrolyte LATP with D50=0.3μm, and the other conditions were the same as in Example 1, thereby preparing a polyurethane hot melt adhesive.

[0052] Comparative Example 1

[0053] A reference polyurethane hot melt adhesive was prepared according to the method of Example 1, except that NASICON-type oxide-based solid electrolyte LATP (D50=0.3 μm) was not added, and the other conditions were the same as those of Example 1. Thus, a reference polyurethane hot melt adhesive was prepared and stored in a vacuum sealed state.

[0054] Comparative Example 2

[0055] A reference polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the addition amount of NASICON-type oxide-based solid electrolyte LATP (D50=0.3 μm) was reduced to 1.00 parts, and the other conditions were the same as those in Example 1. Thus, a reference polyurethane hot melt adhesive was prepared and stored in a vacuum sealed state.

[0056] Comparative Example 3

[0057] A reference polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the amount of 3-mercaptopropyltrimethoxysilane added was reduced to 1.0 part, and the other conditions were the same as those of Example 1, thereby preparing a reference polyurethane hot melt adhesive, which was vacuum sealed and stored.

[0058] Comparative Example 4

[0059] 34.03 parts of polyhexanediol adipate diol POL-538 (Mn=3000 g / mol), 19.45 parts of polyoxypropylene ether diol Voranol-2120 (Mn=2000 g / mol), 10.00 parts of acrylic resin BR-106, 7.50 parts of lithium trifluoromethanesulfonate, 17.50 parts of propylene carbonate, and 0.50 parts of water absorbent Additive TI were added to a reaction bottle, heated to 110°C, and vacuum dehydrated for 2 hours under stirring conditions at 150 r / min; then the temperature was lowered to 80°C, 9.72 parts of 4,4'-diphenylmethane diisocyanate (MDI) and 0.30 parts of stannous octoate were added, and the reaction was carried out under stirring conditions at 150 r / min for 2 hours before discharging to obtain a reference polyurethane hot melt adhesive containing liquid electrolyte, which was vacuum sealed for storage.

[0060] Comparative Example 5

[0061] The reference polyurethane hot melt adhesive was prepared according to the method of Example 1, except that a polyoxyethylene PEO solid electrolyte (Croode Company, brand E-30, with an ionic conductivity of 6.29*10 at room temperature) was used. -6 S / cm) instead of NASICON-type oxide-based solid electrolyte LATP (D50=0.3 μm), and the other conditions were the same as those in Example 1, thereby preparing a reference polyurethane hot melt adhesive.

[0062] Test Case

[0063] The polyurethane hot melt adhesives prepared in the above examples and comparative examples were tested for adhesion performance, heat resistance, and high temperature and high humidity resistance before and after power-on according to the following methods. The results are shown in Table 1.

[0064] (1) Bond strength test at different curing times before power on: The polyurethane hot melt adhesive obtained in the embodiment and the comparative example was dispensed at 110° C. using a glue dispenser to apply a rectangular glue line of 25 mm*4 mm on a stainless steel substrate; then, another stainless steel substrate was bonded to the stainless steel substrate. After bonding, the sample was cured in an environment of 25° C. and 50% RH for 30 min and 1 d, respectively. The prepared bonding sample was run in the shear direction at a speed of 10 mm / min using a universal material testing machine until the bonding of the sample failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after curing for 30 min and 1 d was calculated based on the bonding area.

[0065] (2) Bond strength after power-on: After the glue is dispensed and cured for 1 day according to the method in (1), the sample to be tested is obtained. The positive and negative wires of the DC power supply are clamped at the two ends of the sample, respectively. The power is applied at a voltage of 48 V for 30 min or at a voltage of 60 V for 20 min. After the power-on is completed, the sample is removed and the prepared bonding sample is run along the shear direction at a speed of 10 mm / min using a universal material testing machine until the sample fails to bond. The maximum force value displayed by the instrument is recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after power-on is calculated based on the bonding area (when the bonding strength is less than 2 MPa, it is removable).

[0066] (3) Heat resistance (80°C): The test samples were cured for 1 day according to the method in (1). The test samples were placed in an oven at 80°C for 20 min. The prepared bonding samples were then run in an 80°C environment at a speed of 10 mm / min along the shear direction using a universal material testing machine until the bonding of the samples failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate in a high temperature environment of 80°C was calculated based on the bonding area.

[0067] (4) High temperature and high humidity resistance (85°C, 85% RH): The test sample was obtained after curing for 1 day according to the method in (1). The test sample was placed in a high temperature and high humidity oven at 85°C and 85% RH for 7 days. The prepared bonding sample was run in the shear direction at a speed of 10 mm / min using a universal material testing machine until the bonding of the sample failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after high temperature and high humidity aging was calculated based on the bonding area.

[0068] Table 1

[0069]

[0070] It can be seen from the results of Examples 1 to 7 that the polyurethane hot melt adhesive provided by the present invention not only has a significant decrease in bonding strength (dropped to below 2MPa) after power-on, and has detachability, but also has a fast curing speed, high bonding strength, good heat resistance, high temperature and high humidity resistance, and excellent bonding performance. From the results of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 5, it can be seen that no oxide-based or sulfide-based solid electrolyte is added, or the amount of solid electrolyte added is too small, or a polymer-based solid electrolyte is added, the bonding strength of the polyurethane hot melt adhesive after power-on is much higher than 2MPa, and it is not detachable. At the same time, the bonding strength, heat resistance, and high temperature and high humidity resistance of the polyurethane hot melt adhesive before power-on are reduced. From the results of Example 1 and Comparative Example 3, it can be seen that the amount of silane coupling agent added is too small, the bonding strength, heat resistance, and high humidity and high temperature resistance of the polyurethane hot melt adhesive are poor, and the bonding strength decreases less after power-on, and the bonding strength is greater than 2MPa, and it is not detachable. It can be seen from the results of Example 1 and Comparative Example 4 that, compared with the traditional electrically degradable polyurethane hot melt adhesive prepared by adding alkali metal salts and a solvated matrix, the polyurethane hot melt adhesive provided in Example 1 not only has the same electrically degradable performance, but also has the advantages of fast curing speed, excellent bonding performance, good heat resistance, and resistance to high temperature and high humidity.

[0071] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.

Claims

1. A polyurethane hot melt adhesive, characterized in that: The raw materials for preparing the polyurethane hot melt adhesive contain a solid electrolyte, a polyol compound, a polyisocyanate compound, a silane coupling agent, and optionally a tackifying resin, a catalyst, and a water absorbent; the solid electrolyte is an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte; the mass ratio of the solid electrolyte, the polyol compound, and the silane coupling agent is (5-35):100:(5-25).

2. The polyurethane hot melt adhesive according to claim 1, characterized in that: The content of the solid electrolyte is 5 to 15 parts by weight, the content of the polyol compound is 45 to 65 parts by weight, the content of the polyisocyanate compound is 10 to 20 parts by weight, the content of the silane coupling agent is 5 to 10 parts by weight, the content of the tackifying resin is 0 to 15 parts by weight, the content of the catalyst is 0 to 2 parts by weight, and the content of the water absorbent is 0 to 2 parts by weight; Optionally, the ionic conductivity of the solid electrolyte at room temperature is 10 -4 S / cm or more; Optionally, the D50 or D90 particle size of the solid electrolyte is 0.3 to 30 μm.

3. The polyurethane hot melt adhesive according to claim 1, characterized in that: The number average molecular weight of the polyol compound is 1000 to 4000 g / mol; Optionally, the polyol compound is selected from at least one of polyester polyol, polyether polyol, polycarbonate polyol and polyalkylene polyol.

4. The polyurethane hot melt adhesive according to claim 1, characterized in that: The polyisocyanate compound is selected from at least one of isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, hydrogenated xylylene diisocyanate, 1,5-naphthalene diisocyanate, 1,5-pentane diisocyanate, 1,4-phenylene diisocyanate, meta-xylylene diisocyanate, tetramethylxylylene diisocyanate, norbornane dimethylene isocyanate, lysine diisocyanate, triphenylmethane triisocyanate, thiophosphoric acid triphenyl isocyanate and 1,6,11-undecane triisocyanate.

5. The polyurethane hot melt adhesive according to claim 1, characterized in that: The tackifying resin is selected from at least one of thermoplastic acrylic resin, polyurethane resin, rosin resin, petroleum resin, terpene resin, EVA resin and amorphous polyolefin resin.

6. The polyurethane hot melt adhesive according to claim 1, characterized in that: The silane coupling agent is selected from 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl methyl diethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl triethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3- At least one of oxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and 3-isocyanatepropyltrimethoxysilane.

7. The polyurethane hot melt adhesive according to claim 1, characterized in that: The catalyst is selected from at least one of dibutyltin dilaurate, stannous octoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether.

8. The polyurethane hot melt adhesive according to claim 1, characterized in that: The water absorbent is selected from at least one of a molecular sieve desiccant, an oxazolidine dehydrating agent, p-toluenesulfonyl isocyanate and triethyl orthoformate.

9. The method for preparing the polyurethane hot melt adhesive according to any one of claims 1 to 8, characterized in that: The method comprises uniformly mixing a solid electrolyte, a polyol compound, a polyisocyanate compound, a silane coupling agent, and optional tackifying resin, a catalyst and a water absorbent to obtain a polyurethane hot melt adhesive.

10. Use of the polyurethane hot melt adhesive according to any one of claims 1 to 8 in bonding electronic products.

Citation Information

Patent Citations

  • Solid electrolyte-negative electrode binder for lithium-sulfur battery

    CN112409976A

  • Heat-detachable polyurethane hot melt adhesive, preparation raw materials, and preparation method and bonding method of heat-detachable polyurethane hot melt adhesive

    CN114044868A

  • Conversion type transition metal compound-based solid-state battery and preparation method thereof

    CN114256505A

  • Sealing material for protecting membrane electrode of fuel cell and preparation method of sealing material

    CN115050987A

  • Preparation of a solid polymer electrolyte

    FR3130454A1